Perbedaan Efektivitas Teknik Relaksasi Nafas Dalam dan Kompres Hangat dalam Penurunan Nyeri Dysmenorhea - Arni Wianti; Maulida Miftahul Karimah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the differences in the effectiveness of deep breathing relaxation techniques and warm compresses in decreasing dysmenorhea pain in nursing students level II and III in STIKes YPIB Majalengka. This study uses an experimental method with a non equivalent control group approach. The results of the study illustrate that in the deep breath group a probability value of Ï 0.002 <(0.05), while the warm compress group Ï 0.000 (0.05). Conclusion, there is a significant difference in the decrease in the intensity of dysmenorrhea pain when deep breathing relaxation therapy and warm compresses are significant. Keywords: Dysmenorhea, Warm Compresses, Deep Breath Relaxation